Development of a Relay-Based Approach to Enhance Security of Voice Over Internet Protocol in Rayleigh Fading Distribution - Olasunkanmi Fatai, Oseni; Nuraddeen Yahya, Abubakar; Saminu, Sani (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
There is a severe risk to VoIP communication's secrecy, privacy, and integrity when fading signal strength (Rayleigh fading) degrades the encryption techniques, leaving data open to interception and breaches by eavesdroppers. To address the security vulnerabilities brought in by the communication between the source and destination from interference or monitoring from an eavesdropper. This work proposed and developed the model based on the amplify and forward relay system with modifications in which jamming (noise) is used to shield communication between the source and destination from interference or monitoring from an eavesdropper, as relays are devices that can receive a signal and then retransmit it. The proposed developed model was evaluated using the Secrecy capacity (SC) and signal-to-noise ratio (SNR) for both proposed and existing models at the destination and eavesdropper. The SC values obtained for the developed model after adjusting linearly amplified signal, G_0 (linearly amplified version) was set to 2 and SNRs to 2, 6, and 10 dB, for the destination and eavesdropper were 0.3471, 0.4904, and 0.6019, and 0.257, 0.3664, and 0.4545, respectively. On the other hand, at the same SNRs, the destination SC values for the traditional model were 0.298, 0.4355, and 0.5466, and the eavesdropper values were 0.257, 0.3644, and 0.4545. This study shows that using the relay strategy significantly improves system performance, VoIP security, and dependability Compared to previous approaches.